FMRI study of neural sensitization to hedonic stimuli in long‐term, daily cannabis users. Issue 10 (11th May 2016) - Filbey, Francesca M.; Dunlop, Joseph; Ketcherside, Ariel; Baine, Jessica; Rhinehardt, Tyler; Kuhn, Brittany; DeWitt, Sam; Alvi, Talha
Abstract: Although there is emergent evidence illustrating neural sensitivity to cannabis cues in cannabis users, the specificity of this effect to cannabis cues as opposed to a generalized hyper‐sensitivity to hedonic stimuli has not yet been directly tested. Using fMRI, we presented 53 daily, long‐term cannabis users and 68 non‐using controls visual and tactile cues for cannabis, a natural reward, and, a sensory‐perceptual control object to evaluate brain response to hedonic stimuli in cannabis users. The results showed an interaction between group and reward type such that the users had greater response during cannabis cues relative to natural reward cues (i.e., fruit) in the orbitofrontal cortex, striatum, anterior cingulate gyrus, and ventral tegmental area compared to non‐users (cluster‐threshold z  = 2.3, P  < 0.05). In the users, there were positive brain‐behavior correlations between neural response to cannabis cues in fronto‐striatal‐temporal regions and subjective craving, marijuana‐related problems, withdrawal symptoms, and levels of THC metabolites (cluster‐threshold z  = 2.3, P  < 0.05). These findings demonstrate hyper‐responsivity, and, specificity of brain response to cannabis cues in long‐term cannabis users that are above that of response to natural reward cues. These observations are concordant with incentive sensitization models suggesting sensitization of mesocorticolimbic regions and disruption of natural reward processes following drug use. Although the cross‐sectional nature of this study does not provide information on causality, the positive correlations between neural response and indicators of cannabis use (i.e., THC levels) suggest that alterations in the reward system are, in part, related to cannabis use. Hum Brain Mapp 37:3431–3443, 2016 . ©2016 The Authors Human Brain Mapping Published by Wiley Periodicals, Inc.